RENAL CALYCEAL MICROLITHIASIS - A. Madani; S. J. Janatiy; S. T. Esfahani N. Hajizadeh (Acta Medica Iranica, 2005)
Hematuria is one of the most common genitourinary findings in children and extensive evaluation frequently fails to establish its etiology. ‎A known cause of hematuria in children is nephrolithiasis. Ultrasound is a good method for diagnosis, but calculi less than 5 mm in diameter may not have a posterior shadow. Calyceal microlithiasis (CM) is characterized by presence of hyperechogenic spots less than 3 mm in diameter in renal calyces that are recognized by high resolution ultrasound. In this report, 200 children presenting with microscopic or macroscopic hematuria, dysuria, pyuria and recurrent urinary tract infection, occurring alone or in combination, underwent renal ultrasound at 3.5 MHZ and 7.5 MHZ. Although in 117 cases renal ultrasound at 3.5 MHZ reported normal findings, renal ultrasound at 7.5 MHZ revealed CM in 63.6% of patients presenting with hematuria. ‎There was a history of urolithiasis in one first or second degree relative of 72.4% of the patients. ‎Hypercalciuria was presented in 9.6% and hyperuricuria in 32% of the patients. We recommend that children who are either at greater risk of renal stones, or are highly suspected to be so, be referred for renal ultrasound screening at 3.5 and 7.5 MHZ concurrently.